White Matter Injury in Newborns with Congenital Heart Disease-A Diffusion Tensor Imaging Study - Mulkey, Sarah B. (2014)
BACKGROUND: Brain injury is observed on brain magnetic resonance imaging preoperatively in up to 50% of newborns with congenital heart disease. Newer imaging techniques such as diffusion tensor imaging provide sensitive measures of the white matter. The objective of this study was to evaluate the diffusion tensor imaging analysis technique of tract-based spatial statistics in newborns with congenital heart disease. METHODS: Term newborns with congenital heart disease that would require surgery at less than one month of age were prospectively enrolled (n = 19). Infants underwent preoperative and postoperative brain magnetic resonance imaging with diffusion tensor imaging. Tract-based spatial statistics, an objective whole brain diffusion tensor imaging analysis technique, was used to determine differences in white matter fractional anisotropy between infant groups. Term control infants were also compared to congenital heart disease infants. Postmenstrual age was equivalent between congenital heart disease infant groups and between congenital heart disease and control infants. RESULTS: Ten infants had preoperative brain injury, either infarct or white matter injury, by conventional brain magnetic resonance imaging. The technique of tract-based spatial statistics showed significantly lower fractional anisotropy (P <0.05, corrected) in multiple major white matter tracts in the infants with preoperative brain injury compared to infants without preoperative brain injury. Fractional anisotropy values increased in the white matter tracts from the preoperative to the postoperative brain magnetic resonance imaging correlating with brain maturation. Control infants showed higher fractional anisotropy in multiple white matter tracts compared to infants with congenital heart disease. CONCLUSION: Tract-based spatial statistics is a valuable diffusion tensor imaging analysis technique that may have better sensitivity in detecting white matter injury compared to conventional brain magnetic resonance imaging in term newborns with congenital heart disease.